Apical extrusion of sodium hypochlorite irrigation during root canal treatment using monoject or hypodermic irrigation needle (Bangladesh Journal of Medical Science, 2016)
Objective: Sodium hypochlorite has been routinely delivered into the pulp canal via irrigation needle. The study aimed at to determine the advantage and disadvantage of apical extrusion of sodium hypochloride using monoject or hypodermic irrigation needle in root canal treatment.Materials and Methods: Eighty single rooted teeth with closed apices were used in this in vitro study to determine apical extrusion of sodium hypochlorite using the gel diffusion technique. Extracted human anterior teeth were used as study samples. Monoject (size 27G) and hypodermic (27G× ½, 0.40×13mm, Terumo Needle) irrigation needle were used. The highest concentration of 5.25% hypochlorite solution was used for irrigation. To standardize the time diffusion of the dye, the gel was photographed at exactly 20 minutes after the initial irrigation with sodium hypochlorite.Results: A total of 36 out of 40 (90%) teeth in the hypodermic needle group showed positive apical extrusion compared to 14 of 40 teeth (35%) in the monoject group regardless of apical size. The discoloration of agar was clearly obtained after the sample tooth had been irrigated with sodium hypochlorite indicating the sign of apical extrusion. It is therefore; recommend that monoject irrigation needle should be used by students regardless of costs during root canal treatment in the polyclinic or dental clinic due to its safety in order to prevent sodium hypochlorite accident.Conclusion: Monoject needle showed significantly less sodium hypochlorite extrusion compared to hypodermic needleBangladesh Journal of Medical Science Vol.15(4) 2016 p.575-578